A nonsynonymous polymorphism (rs117179004, T392M) of hyaluronidase 1 (HYAL1) is associated with increased risk of idiopathic pulmonary fibrosis in Southern Han Chinese. Issue 6 (4th May 2021) - Liu, Juan; Deng, Yanhan; Wang, Zheng; Mo, Biwen; Wei, Jianghong; Cheng, Zhenshun; Peng, Qingzhen; Wei, Guang; Li, Jingping; Shu, Ying; Yang, Hua; Fang, Shirong; et al.
Abstract: Background: Idiopathic pulmonary fibrosis (IPF) is a genetic heterogeneous disease with high mortality and poor prognosis. Hyaluronidase 1 ( HYAL1 ) was found to be upregulated in fibroblasts from IPF patients, and overexpression of HYAL1 could prevent human fetal lung fibroblast proliferation. However, the genetic correlation between the HYAL1 and IPF or connective tissue diseases related interstitial lung disease (CTD‐ILD) has not been determined. Methods: A two‐stage study was conducted in Southern Han Chinese population. We sequenced the coding regions and flanking regulatory regions of HYAL1 in stage one (253 IPF cases and 125 controls). A statistically significant variant was further genotyped in stage two (162 IPF cases, 182 CTD‐ILD cases, and 225 controls). Results: We identified a nonsynonymous polymorphism (rs117179004, T392M) significantly associated with increased IPF risk (dominant model: OR = 2.239, 95% CI = 1.212–4.137, p  = 0.010 in stage one; OR = 2.383, 95% CI = 1.376–4.128, p  = 0.002 in stage two). However, we did not observe this association in CTD‐ILD (OR = 1.401, 95% CI = 0.790–2.485, p  = 0.248). Conclusion: Our findings suggest that the nonsynonymous polymorphism (rs117179004, T392M) may confer susceptibility to IPF in Southern Han Chinese, but is not associated with susceptibility to CTD‐ILD. Abstract : A nonsynonymous polymorphism (rs117179004, T392M) of hyaluronidase 1 (HYAL1) is associated with increased risk of idiopathic pulmonary fibrosis (IPF) ( p  = 0.002 in allele‐model) but not connective tissue diseases related interstitial lung disease (CTD‐ILD) ( p  = 0.181 in allele‐model) in Southern Han Chinese.